Filmes Langmuir-Blodgett da enzima penicilinase com nanotubos de carbono funcionalizados com PABS para a nanobiotecnologia - Scholl, Fabio Antonio [UNIFESP] (2016)
In this work was studied the interaction of adsorbed penicillinase on Langmuir and Langmuir Blodgett films with the dimyristoylphosphatidic acid (DMPA) phospholipid, which served as bioinspired systems. Carbon nanotubes (CNTs), functionalized with polyaminobenzene sulfonic acid (PABS), had also been incorporated to the mixed Langmuir films, which systems, as well as the interaction between the components present were evaluated by surface pressure measurements, compression isothermal, Brewster's angle microscopy (BAM) and Polarization Modulation-Infrared reflection-adsorption spectroscopy (PM-IRRAS). The monomolecular films were transferred to solid supports using the LB technique, and then characterized by fluorescence spectroscopy, PM-IRRAS, atomic force microscopy (AFM), and by nanogravimetry. After that, it was observed the behavior of the enzyme activity of the films containing penicillinase. The film modification by CNT was considered an important parameter in this work, and its influence not only at immobilization of penicillinase on this thin films, as well as the enzyme's ability to provide the sensory responses were assessed in detail. The Langmuir films containing CNTs and enzymes presented stable, and through the analysis, can be evidenced the structural conservation of the enzyme, and the influence of carbon nanotubes on consecutive transfer of mixed films at liquid interface to the solid substrates. CNTs improved the efficiency of devices for detection of penicillinase by electronic excitation and enhanced the enzyme activity when they were incorporated into the phospholipid support. The LB methodology was efficient in immobilizing the enzyme on field effect sensors, and the modification by CNTs led to increased sensibility and detection range. In this way, the LB film acted in maintaining protein structure, providing a perspective for possible implications in nanotechnology with CNTs incorporation into artificial membranes, directing the use of immobilized enzymes on solid supports for biosensors.